Exploring Differences in Dogs’ and Wolves’ Preference for Risk in a Foraging Task - Marshall-Pescini, Sarah; Besserdich, Ingo; Kratz, Corinna; Range, Friederike (Frontiers in Psychology, 2016)
Both human and non-humans species face decisions in their daily lives which may entail taking risks. At the individual level, a propensity for risk-taking has been shown to be positively correlated with explorative tendencies, whereas at the species level a more variable and less stable feeding ecology has been associated with a greater preference for risky choices. In the current study we compared two closely related species; wolves and dogs, which differ significantly in their feeding ecology and their explorative tendencies. Wolves depend on hunting for survival with a success rate of between 15 and 50%, whereas free-ranging dogs (which make up 80% of the world dog population), are largely scavengers specialized on human produce i.e. a more geographically and temporally stable resource. Here, we used a foraging paradigm, which allowed subjects to choose between a guaranteed less preferred food vs. a more preferred food, which was however delivered only 50% of the time (a stone being delivered the rest of time). We compared identically raised adult wolves and dogs and found that in line with the differing feeding ecologies of the two species and their explorative tendencies, wolves showed a higher preference for risk-taking than dogs.